Agamben's Impotentiality: Separation, Nonrelationality, and Destituent Potential in The Use of Bodies. (3rd April 2021) - Watkin, William
ABSTRACT: Of all the signature notions that occupy Giorgio Agamben's critique of Western thought, his concept of potentiality may be the most paradigmatic. Aristotle's struggle with potentiality hands on to metaphysics a logical impossibility that he appears to solve with a median term: impotentiality. Yet, in reality, impotentiality would have a significant impact on philosophy, specifically how it comes to be the paradigmatic indifferential suspension of the signature of being for Agamben. Impotentiality occupies an ambiguous position in Agamben's early work. Agamben criticises its logic while associating it with possibilities for a future mode of thought. This idea comes to full expression in The Use of Bodies, which moves us towards a mode of being beyond the suspension of ontology that impotentiality performs. Using the axiom of separation from Alain Badiou's set theory, this article asks if Agamben's articulation of impotentiality is a new avenue for being and existence or the limit beyond which indifferential thought cannot pass.